Prevention of ankle sprains in volleyball - Bahr, R. (2000)
Although the injury rate in volleyball is lower than that seen in contact team sports, the rate of ankle sprains, which account for about half of all acute volleyball injuries, is comparable to that found in basketball, soccer or handball. Based on studies from different sports, but with a focus on volleyball, this lecture will review current status on injury mechanisms, risk factors and prevention strategies for ankle sprains. Ankle sprains in volleyball mainly occur at the net when landing on the foot of an opponent or a teammate after blocking or attacking. The most important risk factor is previous ankle injury, and there appears to be a profound increase in injury risk during the first 6-12 months after an ankle sprain. Four main intervention strategies have been formulated for volleyball which are (1) rule changes to reduce the conflict zone under the net where an attacker may land on a blocker's foot or vice versa, (2) the use of tape or ankle braces as external ankle protection (3) specific technical training on take-off and landing technique during attack and two-man blocks and (4) proprioceptive training after ankle injury. Most studies indicate that appropriately applied braces, tape, or orthoses protect against reinjury in previously injured ankles without adversely affecting performance, whereas there appears to be no effect for previously uninjured ankles. Athletes with a sprained ankle should complete supervised rehabilitation before returning to practice or competition, and wear an appropriate orthosis for at least 6 months. Awareness training, skill improvement and proprioceptive training also appear to have beneficial effects. (2000 Pre-Olympic Congress, Sports Medicine and Physical Education, International Congress on Sport Science, 7-13 September - Brisbane, Australia 2000)